2020
DOI: 10.1038/s41408-020-00347-6
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in treatment and outcomes in multiple myeloma: a multiple myeloma research foundation analysis

Abstract: Findings on racial differences in survival in multiple myeloma (MM) have been inconclusive. We assessed differences in outcomes between White and Black individuals among 639 newly diagnosed MM patients in the MM Research Foundation CoMMpass registry with baseline cytogenetic data. Survival curves were constructed using the Kaplan-Meier method. Hazard ratios and 95% confidence intervals were derived from Cox proportional hazard regression models. Age, gender, and stage were similar between Whites (n = 526) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
42
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 29 publications
8
42
2
Order By: Relevance
“…Recent data suggest that disparities exist in the use of novel myeloma therapies and suggest that a lack of access to treatment could result in poorer patient outcomes. [22] In one study, receipt of autologous stem cell transplant (ASCT) was associated with improved overall survival among patients with MM; this increased survival was notably higher among White patients compared with Black patients, and adults with higher SES compared to adults with lower SES [23].…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggest that disparities exist in the use of novel myeloma therapies and suggest that a lack of access to treatment could result in poorer patient outcomes. [22] In one study, receipt of autologous stem cell transplant (ASCT) was associated with improved overall survival among patients with MM; this increased survival was notably higher among White patients compared with Black patients, and adults with higher SES compared to adults with lower SES [23].…”
Section: Discussionmentioning
confidence: 99%
“…), meaning that ASCT can overcome biological differences among racial subgroups or that equality of treatment overcomes all racial disparities. 16 , 17 , 18 A recent study by Munshi et al conducted on army veterans showed that O.S. disparities across different races are lost and possibly reversed when all patients have the same insurance and access to health system providers.…”
Section: Introductionmentioning
confidence: 99%
“…13,40 In previous venetoclax monotherapy and combination therapy studies, improved responses to venetoclax were observed in patients with t(11;14) RRMM. 13,14,20 [41][42][43] Notably, Black patients with MM are less likely to receive triplet therapies or frontline stem cell transplantation, 43 the latter of which improves survival in patients with t(11;14). 42 The limited number of Black or African American patients enrolled in this study, of which only 3 had t (11;14), precludes assessment of outcomes by race and supports the observed underrepresentation of racial minorities in cancer trials in general.…”
Section: Discussionmentioning
confidence: 99%